Efeitos do fósforo do solo no desenvolvimento inicial de Genipa americana L. - Valeri, Sérgio Valiengo [UNESP]; Puerta, Rogério; Da Cruz, Mara Cristina Pessôa [UNESP] (My University, 2003)
A greenhouse experiment was carried out to evaluate the effects of soil phosphorus in the development of plants of Genipa americana L. Five doses of P (0, 50, 100, 200, and 400 mg dm -3) were applied in pots with 10 dm 3 of three Neossolos Quartzarênicos (NQ 1, NQ 2 and NQ 3) and one Latossolo Vermelho (LV), that were used in an experiment with Eucalyptus plants during three months. After this period, the soils were analyzed and a 30 cm height seedling of G. americana was planted in each pot. The experiment design was completely randomized, in 5 × 4 factorial scheme, with five replications. The largest biomass of the stem was obtained with 45 mg dm -3 of P in the soil NQ 1 (9% of clay) and 59 mg dm -3 in the soil NQ 3 (14% of clay). In the LV (40% of clay), the biomass of the stem increased linearly in the band of 3 to 148 mg dm -3 of P. The phosphorus critical level in the soil for 80% of the steam and leaves dry matter production of G. americana at planting phase is 15 mg dm -3, using an anion-exchange resin as extractor.
Effects of soil phosphorus on initial development of Genipa americana L.
Keywords: Critical level; Fertilizer; Genipa americana; Implantation; Phosphorus; Leaves; Plant stems; Plantations; Biomass; Ion exchange resins; Phosphate fertilizers; Seed; Soil testing; Plants (botany)